Sea buckthorn oil regulates primary myoblasts proliferation and differentiation in vitro - Zhao, Jiamin; Liang, Lin; Zhang, Weipeng; Liu, Xuan; Huo, Guoqiang; Liu, Xiangdong; Lv, Xiaoyang; Zhao, Junxing (In vitro cellular & developmental biology. Animal, 2024)
Skeletal muscle is the main edible part of meat products, and its development directly affects the yield and palatability of meat. Sea buckthorn oil (SBO) contains plenty of bioactive substances and has been recognized as a potential functional food product. The study aimed to explore the effects and possible mechanisms of SBO on sheep primary myoblast proliferation and myogenic differentiation. The results implied that SBO exhibited a pro-proliferative effect on primary myoblasts, along with up-regulated proliferating cell nuclear antigen (PCNA) and Cyclin D1/cyclin-dependent kinase 4 (CDK4) abundances. And, SBO promoted myotube formation by increasing the expression of myogenin. Meanwhile, we found that SBO inhibited the expression of miRNA-292a. Moreover, the regulatory effect of SBO on myogenic differentiation of myoblasts was attenuated by miRNA-292a mimics. Of note, SBO activated protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling pathway and augmented glucose uptake and glucose transporter 4 (GLUT4) content, which might be attributed to AMP-activated protein kinase (AMPK) activation. Additionally, the results were shown that SBO increased the abundance of antioxidative enzymes, including glutathione peroxidase 4 (Gpx4) and catalase. In summary, these data suggested that SBO regulated the proliferation and myogenic differentiation of sheep primary myoblasts in vitro, which might potentiate the application of SBO in muscle growth.